PENGARUH KONSENTRASI IAA DAN BERBAGAI JENIS MEDIA TUMBUH TERHADAP PERTUMBUHAN TANAMAN SELEDRI (Apium graveolens L.) DENGAN SISTEM BUDIDAYA HIDROPONIK FERTIGASI - Amilia Rara Anggraini; Hasan Basri Jumin; Ernita Ernita (DINAMIKA PERTANIAN, 2017)
The purpose of the study was to determine the effect of IAA concentration and various types of media growing on celery plant growth with a fertilizing hydroponic cultivation system in interaction as well as each of the main influences. The design used in this study is the Design of Divided Plots in the form of Complete Randomized Design consisting of two factors. The first factor is IAA (A) with a concentration of 0, 1, 10, 100 ppm while the second factor is Various Types of Growing Media (M), namely Cocopeat, Husk Charcoal, Sawdust Powder, Hydroton. The parameters observed were plant height (cm), economical wet weight (g), root volume (cm3), average net assimilation rate (g /cm2/day), average relative growth rate (g /day), number of tillers (fruit), root canopy ratio (g). The last observation data were analyzed statistically and continued with a BNJ follow-up test at the level of 5%. The results showed that the interaction of IAA concentrations and various types of media grew significantly on the parameters of the plant's wet weight, root volume, and root canopy ratio. The best treatment was found in a combination of treatment of 1.0 ppm IAA concentration and cocopeat growing media. The main effect of IAA concentration was real on all observed parameters. The best treatment is 1.0 ppm IAA concentration. The main influence of various types of media grows significantly for all observational parameters. The best treatment is the cocopeat media.